Occiput posterior position diagnosis: vaginal examination or intrapartum sonography? A clinical review. (March 2014) - Malvasi, A.; Tinelli, A.; Barbera, A.; Eggebø, T.M.; Mynbaev, O.A.; Bochicchio, M.; Pacella, E.; Di Renzo, G.C.
Abstract The occiput posterior (OP) position is one of the most frequent malposition during labor. During the first stage of labor, the fetal head may stay in the OP position in 30% of the cases, but of these only 5–7% remains as such at time of delivery. The diagnosis of OP position in the second stage of labor is made difficult by the presence of the caput succedaneum or scalp hair, both of which may give some problem in the identification of fetal head sutures and fontanels and their location in relationship to maternal pelvic landmarks. The capability of diagnosing a fetus in OP position by digital examination has been extremely inaccurate, whereas an ultrasound approach, transabdominal, transperineal and transvaginal, has clearly shown its superior diagnostic accuracy. This is true not only for diagnosis of malpositions, detected in both first and second stage of labor, but also in cases of marked asynclitism.